An unusual case of severe hypercalcemia: as dehydrated as a bone - Roshan Acharya; Dylan M Winters; Cameron Rowe; Nathan Buckley; Smita Kafle; Bhaskar Chhetri (Greater Baltimore Medical Center, 2021)
Objective: Severe hypercalcemia is a medical emergency. Hyperparathyroidism, malignancy, vitamin D toxicity, infections such as tuberculosis, or systemic illness such as sarcoidosis are all possible etiologies. Among the less studied causes is dehydration. Our objective is to identify dehydration as an etiology of hypercalcemia. Methods: Extensive literature review did not recognize dehydration as an etiology of hypercalcemia. We present a case of dehydration leading to severe hypercalcemia in a 60-years-old female with a presentation of altered mental status and corrected calcium level of 19 mg/dL in the absence of parathyroid abnormality, vitamin D toxicity, systemic disease, or malignancy. Results: Dehydration caused hypercalcemia which led to a feed-forward mechanism and caused further worsening dehydration, worsening kidney function, and severe hypercalcemia. The patient responded very well to intravenous fluid and at the time of discharge had a serum calcium of 9.8 mg/dL with improved mental status back to the baseline. Conclusion: Our literature review demonstrated many causes of hypercalcemia, with dehydration being exceptionally rare. It is our hope that this case report may serve as evidence of one such instance, allowing providers to keep a working differential of dehydration in severely elevated calcium levels.